A Numerical Study of Gravity Wave Propagation Characteristics in the Stratospheric Thermal Duct. Issue 21 (9th November 2018) - Dong, Wenjun; Zhang, Shaodong; Huang, Chunming; Huang, Kaiming; Gong, Yun; Gan, Quan
Abstract: We developed a fully nonlinear, two‐dimensional, numerical model to simulate the long horizontal distance propagations of atmospheric gravity waves in a stratospheric thermal duct. The numerical results show that after the wind disturbance excited by the initial wave forcing enters the duct completely, symmetric and antisymmetric modes can be identified in the horizontal direction. The frequency‐wave number spectrum indicates that various modes with different spatial structures can exist simultaneously in the duct. The primary parameters (horizontal wavelength, vertical wavelength and wave frequency) of the ducted wave packets in a given thermal duct are mainly determined by the horizontal wavelength of the initial wave forcing. The mean ratio of the upward propagating energy to the downward propagating energy in the thermal duct was regarded as an approximation of the power standing wave ratio (PSWR). The time variation of PSWR indicates that the standing wave was formed with the propagation of the ducted waves. During the gravity waves ducted propagation, most wave energy is restricted to the ducting region and dissipates slowly with time. The higher the wave frequency (or the shorter the horizontal wavelength) of the initial wave forcing, the slower the wave energy dissipates. Key Points: The primary parameters of the ducted modes in a given thermal duct are mainly determined by the horizontal wavelength of the initial wave The dynamics of the standing wave in the duct region are related to the initial wave forcing The decay rate of the total energy in the thermal duct is largely affected by the initial wave forcing